Annual Report 2012-2013: transforming lives and landscapes with trees - World Agroforestry Centre (World Agroforestry Centre, 2013)
The year 2012 saw the final phases of the reform process launched by the Consultative Group on International Agricultural Research (CGIAR). All the CGIAR Research Programmes (CRPs) became fully operational during the year and I believe our scientists are now confident about the direction in which they are moving. I welcome the fact that we have established closer collaboration with the Center for International Forestry Research (CIFOR) and our other partners within the framework of CRP 6, which focuses on forests, trees and agroforestry. Although the bulk of our future research will take place under this programme, we will also be making important contributions to several other CRPs, including those related to water, land and ecosystems; climate change; health and nutrition; institutions and markets; and, more generally, agriculture and food security.